FAKTOR-FAKTOR YANG MEMENGARUHI KEJADIAN BAYI BERAT BADAN LAHIR RENDAH (BBLR) DI KOTA DENPASAR (ANALISIS DATA SEKUNDER MENGGUNAKAN UJI REGRESI LOGISTIK) - Luh Made Parayuni Dewanti; Desak Nym Widyanthini (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2023)
Indonesia listed by WHO as occupying the ninth position in the world with percentage of LBW more than 15,5% each year. In 2021 Province of Bali have 2,123 LBW babies and Denpasar City is the first rank of LBW with total 367. This study uses analytical research type with design case control. Sample amounted 267 samples at Wangaya Hospital and Bali Mandara Hospital from January 2020 to October 2022. Sample case are LBW babies with total 89 samples based on method total sampling, while sample control are NBW babies with total 178 samples based on method simple random sampling. Data were analyzed descriptively and relationship between variables used logistic regression test. The results showed three significant variables with LBW, gestational age (OR=17.8;p<0.001), bad obstetric history (OR=0.07;p=0.009), and ANC examination (OR=54.9;p<0.001). However, four variables no significant with LBW, mother's age, parity, disease history, and pregnancy complications. From the study results, expected that the study is able to routinely carry out pregnancy checks, as input for related institution to actively convey factors and risks of LBW, as well as input for the need for further research with different methods and varied research. Keywords: maternal factors, individual disease control factors, LBW, NBW